Versatile magnetorheological plastomer with 3D printability, switchable mechanics, shape memory, and self-healing capacity. (20th October 2019) - Qi, Song; Fu, Jie; Xie, Yuanpeng; Li, Yaping; Gan, Ruyi; Yu, Miao
Abstract: The rapid advancement in soft actuators imposes an emergent requirement for soft stimuli-sensitive materials that are deformable and stiffness variable and show designability and adaptivity. Soft actuators based on magneto-sensitive materials with outstanding magnetic-control performance are highly desirable in research. In this paper, we developed a versatile magnetorheological plastomer (MRP) based on polycaprolactone (PCL)/thermoplastic polyurethane (TPU) polymer blends. The MRP showed 3D printability, switchable mechanics, shape memory, and self-healing properties. The thermoplasticity of the matrix enables fused deposition modeling 3D printing, which affords the MRP excellent shape designability. By taking advantage of the phase transition and magnetorheological effect, the dramatic switchable mechanical properties of MRP can be triggered by thermal stimulus and magnetic field. The influences of matrix, particle content, temperature and magnetic field on the mechanical properties were discussed comprehensively, and possible physical mechanisms were proposed so that the result can be qualitatively explained. Based on hybrid crystalline and amorphous regions of PCL and TPU, the MRP exhibited superior shape memory and self-healing properties. This work may play an important role in the future development of multifunctional magneto-sensitive material and promote the application of soft actuators in the fields of soft robotics, medical care, and bionics applications.